Sarcoplasmic reticulum calcium ATPase is inhibited by organic vanadium coordination compounds: pyridine-2,6-dicarboxylatodioxovanadium(V), BMOV, and an amavadine analogue - Aureliano, Manuel (2013)
Inorg Chem. 2008 Jul 7;47(13):5677-84. doi: 10.1021/ic702405d